2009
DOI: 10.1038/jes.2009.45
|View full text |Cite
|
Sign up to set email alerts
|

Exposures of preschool children to chlorpyrifos, diazinon, pentachlorophenol, and 2,4-dichlorophenoxyacetic acid over 3 years from 2003 to 2005: A longitudinal model

Abstract: The impact of the US EPA-required phase-outs starting in 2000-2001 of residential uses of the organophosphate (OP) pesticides chlorpyrifos (CPF) and diazinon (DZN) on preschool children's pesticide exposures was investigated over 2003-2005, in the Raleigh-Durham-Chapel Hill area of North Carolina. Data were collected from 50 homes, each with a child initially of age 3 years (OCh) and a younger child (YCh). Environmental samples (indoor and outdoor air, dust, soil) and child-specific samples (hand surface resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…Sweet and salty snacks were defined as highly processed food items like pretzels, popcorn, potato chips, rice cakes, crackers, cookies, and cereal/granola bars. Dietary ingestion is considered a major exposure route of 2,4-D in the general population in the US (Nishioka et al, 2001;Morgan et al, 2004;Wilson et al, 2010). However, scant data are available on the specific foods consumed by adults that contain 2,4-D residues (US FDA, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sweet and salty snacks were defined as highly processed food items like pretzels, popcorn, potato chips, rice cakes, crackers, cookies, and cereal/granola bars. Dietary ingestion is considered a major exposure route of 2,4-D in the general population in the US (Nishioka et al, 2001;Morgan et al, 2004;Wilson et al, 2010). However, scant data are available on the specific foods consumed by adults that contain 2,4-D residues (US FDA, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…E-mail address: morgan.marsha@epa.gov soil, and/or wipes collected at US residences (Colt et al, 2004;Stout et al, 2009;Wilson et al, 2010;Morgan et al, 2014;Trunnelle et al, 2014). In addition, studies across the US have reported measureable concentrations of several different pesticide biomarkers including 2,4-dichlorophenoxyacetic acid (2,4-D), 3,5,6-trichloro-2-pyridinol (TCP), 3-phenoxybenzoic acid (3-PBA), and pentachlorophenol (PCP) in the urine of the general adult population (Berkowitz et al, 2003;Barr et al, 2005a;Meeker et al, 2005;Morgan et al, 2008a;CDC, 2009;Barr et al, 2010;McKelvey et al, 2013;Trunnelle et al, 2014) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Exposures to OPP and PYR could occur through inhalation, dermal absorption, or ingestion, with dietary ingestion generally found to be the major route of exposure. [3][4][5]11,12] OPP and PYR present in the diet may result from treatment of crops during the growing season and during storage, treatment of animals against insect-borne diseases, and/or contamination during food preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Naeher et al reported the association between selfreported insecticide use and exposure to both pyrethroids and organophosphates in the US and found a significant association only for pyrethroids (69). It is likely that the association between domestic insecticide use and pyrethroid exposure from studies in the US is more consistent than the association with organophosphate exposure; this is because the use of pyrethroid active ingredients in domestic insecticides has increased due to the the implementation of stricter regulations on the sale of organophosphates for domestic use (76).…”
Section: Products In the Home: Personal Care Products And Insecticidesmentioning
confidence: 53%